2023
DOI: 10.3390/ijerph20166563
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Experiences of Care in Portuguese Nursing Homes during the COVID-19 Pandemic: A Focus Group Study

Abstract: The COVID-19 pandemic has had a considerable influence on long-term care facilities, exposing the shortcomings of nursing homes in implementing recommendations by health authorities. It also emphasizes the need for a nursing management model customized to the vulnerable status of residents, organizational demands, and occupational nursing requirements. We aimed to characterize the perspectives of nurses who have experienced COVID-19 in nursing homes regarding measures implemented to avoid or manage outbreaks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Restrictions hastened residents’ physical and cognitive decline [ 21 , 22 ]. Family caregivers experienced loneliness [ 21 , 23 ], guilt, and anxiety at the irreplaceable lost time together [ 1 , 24 ]. As these impacts of COVID-19 restrictions emerged, one or two essential family caregivers were allowed into residents’ rooms to provide some care [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Restrictions hastened residents’ physical and cognitive decline [ 21 , 22 ]. Family caregivers experienced loneliness [ 21 , 23 ], guilt, and anxiety at the irreplaceable lost time together [ 1 , 24 ]. As these impacts of COVID-19 restrictions emerged, one or two essential family caregivers were allowed into residents’ rooms to provide some care [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coe and Werner’s analysis of population health survey data found that family caregivers of long-term care residents contributed 37.4 h of care per month on average, which is roughly equivalent to an extra full-time shift of paid providers per month [ 16 ]. The long-term care staffing shortages that existed prior to the pandemic [ 8 , 24 ] were exacerbated by restrictions on what family caregivers could do [ 17 ], leading to increased work to follow COVID-19 policies [ 23 , 25 ] and trying to meet residents’ increased care and socioemotional needs [ 16 , 17 ] while supporting family visitations through window visits or with technology such as iPads or ZOOM [ 6 , 26 , 27 ]. The pandemic reinforced that family involvement in long-term care is essential for promoting person-centered care, improving the well-being of residents, and fostering a collaborative approach to caregiving [ 5 , 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation